2005
DOI: 10.1111/j.1523-1755.2005.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic of end-stage renal disease in people with diabetes in the United States population: Do we know the cause?

Abstract: We hypothesize that an epidemic of ESRD has occurred in people with diabetes in the United States population over the last two decades. The nature of the factor responsible for the epidemic and the reasons it affects patients with type 2 diabetes particularly are unknown. Research efforts to identify the putative factor deserve high priority, as does a commitment of resources to provide care for the burgeoning number of patients with ESRD and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
166
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(173 citation statements)
references
References 38 publications
0
166
0
7
Order By: Relevance
“…[1][2][3][4] In contrast, the contribution of sex to diabetic renal disease is poorly understood. The existing data are contradictory: studies report that diabetic females progress either at a faster rate [6][7][8][9][10] or a slower rate [13][14][15][16] than age-matched diabetic men, or that there are no sex differences in the rate of progression. 11,12 This lack of conclusive data on the effects of sex on diabetic renal disease reflects the fact that few studies have addressed this issue and that the studies that did were limited by differences in study populations and methodology and by not specifically addressing factors such as age, hormonal status, duration and type of diabetes, ethnicity, demographic characteristics, blood pressure, blood glucose control, or antihypertensive therapy.…”
Section: Renal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] In contrast, the contribution of sex to diabetic renal disease is poorly understood. The existing data are contradictory: studies report that diabetic females progress either at a faster rate [6][7][8][9][10] or a slower rate [13][14][15][16] than age-matched diabetic men, or that there are no sex differences in the rate of progression. 11,12 This lack of conclusive data on the effects of sex on diabetic renal disease reflects the fact that few studies have addressed this issue and that the studies that did were limited by differences in study populations and methodology and by not specifically addressing factors such as age, hormonal status, duration and type of diabetes, ethnicity, demographic characteristics, blood pressure, blood glucose control, or antihypertensive therapy.…”
Section: Renal Diseasementioning
confidence: 99%
“…However, in the setting of diabetes mellitus (DM), this sex difference in the incidence and progression of renal disease has not been fully established. Whereas some studies report that male sex is a risk factor for the development and progression of renal disease in diabetes, [6][7][8][9][10] others indicate no sex differences 11,12 or even increased risk in women. [13][14][15][16] The reasons for these contradictory reports are numerous, including different patient populations studied, different study designs, and inadequate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Vascular complications of diabetes mellitus (DM) are categorized as either microvascular complications, such as diabetic retinopathy, diabetic nephropathy and diabetic neuropathy or macrovascular complications, including diabetic cardiovascular complications (1)(2)(3). Global burden of high prevalence diabetes are worldwide own to cardiovascular interventions and renal failure therapy (1).…”
Section: Contextmentioning
confidence: 99%
“…There are several factors in addition to some growth in CKD. Two studies have argued against better patient survival in high-risk patients as the proximate reason for more ESRD (24,25). Some have concluded that there must be a greater risk for disease progression to account for this discrepancy (25).…”
Section: Is the Ckd Epidemic Growing?mentioning
confidence: 99%
“…Two studies have argued against better patient survival in high-risk patients as the proximate reason for more ESRD (24,25). Some have concluded that there must be a greater risk for disease progression to account for this discrepancy (25). However, there may be a greater willingness of patient and provider to accept treatment especially in the older segments of the population.…”
Section: Is the Ckd Epidemic Growing?mentioning
confidence: 99%